Should engineers have more influence on safety? A view from a member of the United States Chemical Safety Board. Issue 3 (25th June 2019) - Engler, Rick
Abstract: Major chemical incidents continue at industrial facilities in the United States. More effective arguments for a "business case" for safety are necessary, but not sufficient, to achieve prevention. Findings of the U.S. Chemical Safety and Hazard Investigation Board from its investigations at two oil refineries suggest that greater authority for engineers and safety professionals is a critical requirement to prevent future incidents. Engineers and safety professionals should have greater influence on process design, commissioning, maintenance, and capital and operating budgets. They should be part of the firm's highest level of management and Board of Directors. Engineers should also have the ability to make process hazard analysis an ongoing process and to directly communicate hazards and needed safeguards to senior corporate leaders.